A Comparative Study of Green Geopolymer Concrete Using Fly Ash - Gurlhosur, Shri Krishna; Kamdod, Abdul Samad M; Patil, V.M.; B, Sreekanth (Kathmandu University Journal of Science, Engineering and Technology, 2015)
In this work, the long-term properties of low-calcium fly ash-based geopolymer concrete were studied. The long-term properties included in the study were compressive strength, sulfate resistance, and sulfuric acid resistance. Fly ash-based geopolymer concrete in this study utilized the low-calcium (ASTM Class F) dry fly ash as the source material. The alkaline liquid comprised a combination of sodium silicate solution and sodium hydroxide solids in flakes or pellets form dissolved in water. The coarse aggregates were crushed granite-type aggregates comprising 16 mm, and the fine aggregate was fine sand. High-range water reducer superplasticizer was used to improve the workability of fresh geopolymer concrete. The mixture proportions used in this study were developed based on a previous study on fly ash-based geopolymer concrete. Two different mixing ratios, M15 and M20, were used for the fly ash concrete, cement concrete, and a mixture of cement+fly ash concrete specimens. Test specimens were manufactured in the laboratory using the equipment normally used for Portland cement concrete, such as a pan mixer and steel molds. For sulfate resistance tests, the test specimens were immersed in 4% sodium sulfate solution for a period of exposure up to one week. The sulfate resistance was evaluated based on the change in mass, change in length, and change in compressive strength of the specimens after sulfate exposure. The test specimens were 150x150x150 mm cubes. The sulfuric acid resistance of concrete was also studied. The concentration of sulfuric acid solution was 5% for soaking concrete specimens. The sulfuric acid resistance of concrete was evaluated based on the mass loss and the residual compressive strength of the test specimens after acid exposure up to one week. For each type of test, companion specimens were prepared and tested to determine the 7th day and 28th day compressive strength.